Agenda-Setting Theory on Social Media: Does the Algorithm Control Information? - Šmigić, Jovana N. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
In modern society, which witnesses an expansive increase of digital technologies in everyday life, digital literacy has become almost essential for the functioning of individuals, communities, institutions, states, and interpersonal relationships. The transmission of information, once dominated by traditional media such as newspapers and television, has largely been replaced by social networks, online portals, and trends that emerge on the Internet as a result of commentary on current topics by public figures—so called influencers—and other prominent online personalities, or through the collective interest of digitally connected communities in particular issues. In 1972, Maxwell McCombs and Donald Shaw introduced the agenda-setting theory, which suggests the manipulation of public opinion through the media, and they substantiated this by researching the relationship between current topics in the media and the issues that people consider important. Today, when social networks increasingly play the role of media, this theory takes on a different form. By examining content on TikTok, current topics, popular people, hashtags, and global events, it becomes evident that social networks indeed exert a significant influence on public opinion. However, content on social networks can be created and published by anyone, and such content does not undergo verification, which allows individuals to disseminate information, opinions, advice, or claims. This, however, does not mean that everything on social networks is true, especially if we take into account the possibilities of paid advertising, the virality of content, the influence of algorithms, and the control of censorship exercised by these platforms. The greatest attention is typically directed toward content that accumulates the highest number of likes, views, comments, or sparks discussions, thereby achieving popularity. By analyzing past and current conflicts in the world, it can be concluded that social networks may also serve as tools of online warfare—a phenomenon previously unknown in conflicts until recently—while today they even provide live broadcasts from battlefields. Considering that both the percentage of social media users and the time spent on social platforms are increasing daily, users must remain vigilant and aware of the potential for manipulation. It is therefore essential to cultivate a critical stance toward social media content and to carefully examine claims before accepting them as true.